Editorial: Community Adaptation to Photobiomodulation Near-Infrared Based on Post-Partum Culture Care - Rosnani Rosnani (Pediomaternal Nursing Journal, 2021)
Editorial: Community Adaptation to Photobiomodulation Near-Infrared Based on Post-Partum Culture Care